2004
DOI: 10.1002/cjce.5450820123
|View full text |Cite
|
Sign up to set email alerts
|

Isomérisation du n‐hexane sur des catalyseurs Ni‐WOx/Al2O3‐SiO2

Abstract: Isomerization of n‐hexane into bi‐ and tri‐branched products was studied at atmospheric pressure on Ni‐WOx/Al2O3‐SiO2 catalysts. Two groups of catalysts (A and B) were prepared by using the sol‐gel method. The objective of the present study is the selection of the catalyst having the best isomer (bi‐ and tri‐branched) yield under optimum operating conditions (reaction temperature, reduction temperature, flow duration, etc.). The results show that the introduction of tungsten (group B) modifies siginificantly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In previous works, [22][23][24][25] we found that Ni-WO x /SiO 2 -Al 2 O 3 catalysts are deactivated during straight chain paraffin's hydroisomerization because of the formation of carbon deposits that block pores and surface active sites. To quantify the amount of coke deposited during the reaction, after reaching the steady state (120 min) and to obtain information about how coke distributes over the catalyst, TPO analyses of the carbonaceous deposits were conducted on all the spent catalysts.…”
Section: Coke Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous works, [22][23][24][25] we found that Ni-WO x /SiO 2 -Al 2 O 3 catalysts are deactivated during straight chain paraffin's hydroisomerization because of the formation of carbon deposits that block pores and surface active sites. To quantify the amount of coke deposited during the reaction, after reaching the steady state (120 min) and to obtain information about how coke distributes over the catalyst, TPO analyses of the carbonaceous deposits were conducted on all the spent catalysts.…”
Section: Coke Characterizationmentioning
confidence: 98%
“…One of the most widely used techniques is temperature-programmed oxidation (TPO). [12][13][14][15][16][17][18][19][20][21] In a previous work, we have demonstrated that Ni-WO x / SiO 2 -Al 2 O 3 catalysts can be excellent candidates for catalytic hydroisomerization (up to 79.2 and 70% selectivity to isomers in the case of n-hexane and n-heptane, respectively) 22,23 and dewaxing (the selectivity to isomers, in the case of n-decane, amounts to 55% at a conversion of 42.3%); 24,25 however, they exhibit a decay in activity due to carbonaceous deposits. Thus, in this contribution, we report a study of the nickel-tungsten supported on amorphous silica-alumina catalysts deactivation.…”
Section: Introductionmentioning
confidence: 99%